Inappropriate sinus tachycardia or…something else?. Issue 6 (17th October 2019) - Muresan, Lucian; Le Bouar, Ronan; Greciano, Stephane; Muresan, Crina; Schiau, Serban; Cismaru, Gabriel; Levy, Jacques
Abstract: We report the case of a 45‐year old female patient with a past medical history of rheumatoid arthritis who presented to our cardiology department with a suspicion of inappropriate sinus tachycardia. Echocardiography showed a nondilated left ventricle with a preserved ejection fraction. A careful reinterpretation of her 12‐lead ECG reoriented the diagnosis toward an incessant atrial tachycardia. The diagnosis was confirmed by an electrophysiologic study performed with an electro‐anatomic mapping system, which identified the origin of the tachycardia at the level of the right atrial appendage. Radiofrequency ablation of the ectopic focus eliminated the tachycardia and improved the patient's symptoms. Abstract : We present a rare case of ectopic atrial tachycardia originating from the right atrial appendage masquerading as inappropriate sinus tachycardia in a young female patient with rheumatoid arthritis.